Why do paediatricians prescribe antibiotics? Results of an Italian regional project - Di Mario Simona; Gagliotti Carlo; Marchi Massimiliano; Moro Maria; Resi Davide (BMC, 2009)
Abstract Background To investigate determinants of antibiotic prescription in paediatric care, as a first step of a multilevel intervention to improve prescribing for common respiratory tract infections (RTIs) in a northern Italian region with high antibiotic prescription rate. Methods A two-step survey was performed: in phase I, knowledge, and attitudes were explored involving all family and hospital paediatricians of Emilia-Romagna and a sample of parents. In phase II, patient care practices were explored in a stratified random sample of visits, both in hospitals and family physician's clinics; parent expectations were investigated in a sub-sample of these visits. Results Out of overall 4352 visits for suspected RTIs, in 38% of children an antibiotic was prescribed. Diagnostic uncertainty was perceived by paediatricians as the most frequent cause of inappropriate prescription (56% of 633 interviewed paediatricians); but, rapid antigen detecting tests was used in case of pharyngitis/pharyngotonsillitis by 36% and 21% of family and hospital paediatricians only. More than 50% of paediatricians affirmed to not adopt a "wait and see strategy" in acute otitis. The perceived parental expectation of antibiotics was not indicated by paediatricians as a crucial determinant of prescription, but this perception was the second factor most strongly associated to prescription (OR = 12.8; 95% CI 10.4 - 15.8), the first being the presence of othorrea. Regarding parents, the most important identified factors, potentially associated to overprescribing, were the lack of knowledge of RTIs and antibiotics (41% of 1029 parents indicated bacteria as a possible cause of common cold), and the propensity to seek medical care for trivial infections (48% of 4352 children accessing ambulatory practice presented only symptoms of common cold). Conclusion A wide gap between perceived and real determinants of antibiotic prescription exists. This can promote antibiotic overuse. Inadequate parental knowledge can also induce inappropriate prescription. The value of this study is that it simultaneously explored determinants of antimicrobial prescribing in an entire region involving both professionals and parents.